Immediate Analgesic Effect of Acupuncture in Patients With Primary Dysmenorrhea: A fMRI Study - Wang, Yanan; Xu, Jing; Zhang, Qing; Zhang, Qi; Yang, Ya; Wei, Wei; Guo, Xiaoli; Liang, Fanrong; Yu, Siyi; Yang, Jie (Frontiers in Neuroscience, 2021)
Primary dysmenorrhea (PDM) is the common gynecological disease with the characteristic symptom of periodic pain in the lower abdomen. Acupuncture has been considered as a good alternative therapy for PDM. However, the brain mechanism of the analgesic effect of acupuncture is largely unknown. In this study, we combined task and resting functional magnetic resonance imaging (fMRI) data to investigate the potential brain mechanism of immediate effect of acupuncture intervention on pain intensity of PDM. The task fMRI study found the rostral anterior cingulate cortex (rACC) and right supplemental motor area activated during real acupuncture. In addition, the change of functional connectivity (FC) between rACC and left precentral gyrus was also positively correlated with the short-time pain analgesia in PDM patients after acupuncture treatment, furthermore, the same FC at baseline also associated with the subsequent clinical responses. The findings supported the importance of rACC- left precentral gyrus rsFC in the modulation of pain intensity of PDM patients through acupuncture. Our study also implicated that the rACC and precentral FC could be a useful marker to predict the immediate analgesic effect of acupuncture for PDM.